PENGARUH FARTLEK DAN INTERVAL TRAINING TERHADAP PENINGKATAN DAYA TAHAN KOMUNITAS PARKOUR AND FREERUN PONTIANAK - Miftahuddin, Miftahuddin; Triansyah, Andika; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractEndurance is the body's ability to work in a relatively long time without experiencing fatigue which means, the body always needs oxygen (O2) to produce energy. Measurement of durability can be done by measuring the value of maximum oxygen consumption (VO2 Max). The general purpose of the research was to determine the effect of fartlek and interval training on increasing endurance and knowing which groups had a higher average endurance increase among the treated groups.This research used a pre-experiential design, namely two group pretest-posttest design. The population in this research were all in the Pontianak Parkaur and Freerun Community totaling 20 people.Based on the research objectives it can be summarized as follows: There is an effect of Fartlek training on increasing endurance, (? = 0.012). There is an effect of Interval Training on increasing endurance, (? = 0.017) and there is no significant difference between Fartlek training and Interval Training on increasing endurance, (? = 0.712)Based on the results of the  research showed that the method of developing fartlek training and interval training can be used as an effective and efficient training program to increase endurance. With a note of practice must be programmed systematically, regularly, and discipline Keywords:   Endurance  (VO2  Max),  Fartlek,  Interval  Training